Legal Status of Physical Data and Legal Data of Ownership Rights to Land Submerged by Rob Water in Pekalongan City - Farisi, Salman Al; Hamzani, Achmad Irwan (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
Land as a limited resource but with a relatively stagnant amount requires guarantees of certainty and legal protection. The tidal flood that hit Pekalongan City caused confusion regarding the status of Physical Data and Legal Data of land ownership rights. This study describes the impact of tidal floods on physical data and legal data of land ownership rights along with its solutions in Pekalongan City. The research method uses sociological juridical using qualitative descriptive research specifications. The results of this study explain that land submerged in tidal floods in Pekalongan City cannot be said to be destroyed. Landowners can maintain their land boundary markers by using longer stakes as signs of physical data of the land area. Then, for owners who are interested in knowing complete legal data on the land, they can submit a Land Registration Certificate (SKPT) or a re-measurement application at the National Land Agency which contains detailed data, both physical data and legal data on the land concerned.